CRYPTOCURRENCIES AND THEIR PROBLEMS IN THE FINANCIAL SECTOR - Shirinboeva Dilora Dilmurod qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article focuses on cryptocurrencies and their challenges for the digital financial industry, as well as their advances as a result of new interactions with modern financial systems. In our article, we considered it necessary to give our scientific assumptions about how the cryptocurrency system is related to modern financial systems, their work in the global financial sphere and the problems that can be encountered in this area.